ANALYSIS OF THE EFFECT OF BUILDING INFORMATION MODELLING (BIM) TECHNOLOGY IMPLEMENTATION ON OCCUPATIONAL SAFETY AND HEALTH (K3) TO MINIMIZE THE LEVEL OF WORK ACCIDENTS DURING PROJECT EXECUTION PHASE CASE STUDY: ITB INNOVATION PARK BUILDING CONSTRUCTION PROJECT - Ranandya Purwandi, Fahry
Construction remains an industry with a high risk of accidents that result in human casualties, property damage, and environmental harm. According to research by the International Labour Organization (ILO), there are 60,000 fatal workplace accidents at construction project sites annually. In 2017, data from the Ministry of Public Works and Housing (PUPR) indicated that 32% of annual workplace accidents in Indonesia occur in the construction sector, making it the largest contributor to workplace accidents. However, conventional safety planning seems unable to ensure an adequate level of health and safety during the construction process. Therefore, new identification methods are needed to improve Occupational Health and Safety (OHS) standards. Building Information Modeling (BIM) presents opportunities to identify and address safety hazards that are difficult to achieve with traditional planning methods, such as safety rule checks and design validation, education, training, and communication. Thus, this study aims to identify the impact of implementing Building Information Modeling (BIM) technology on the Occupational Health and Safety (OHS) to minimize the level of workplace accidents in construction projects during the project execution phase. To answer the objectives of this study, both qualitative and quantitative methods were used. A qualitative method in the form of a literature review was used to identify BIM variables that can influence OHS to minimize the level of workplace accidents. A quantitative method in the form of a questionnaire was used to identify the influence levels of 8 variables obtained using the Relative Importance Index (RII) method. Additionally, qualitative methods were also used in the form of interviews, processed using NVIVO 12 Pro software, to validate the questionnaire results with 8 respondents from the engineering division and 6 respondents from the safety, health, and environment (SHE) division at PT Wika Gedung on the ITB Innovation Park Building Project. Through the 8 research variables on the impact of BIM on OHS to minimize workplace accidents during the project execution phase, it was found that 7 out of the 8 variables were proven to be influential based on the results of questionnaires and interviews with BIM and OHS experts on the reviewed project. The variable coded V-5 had the highest influence level, with a score of 0.982 based on RII analysis. Meanwhile, the variables already implemented in the reviewed project were the variables coded V-4 Safety Communication and V-5 Safety Observation and Design Validation. Furthermore, based on expert interviews, the implementation of BIM will have a more significant impact on OHS if integrated with other technologies such as Virtual Reality (VR), Augmented Reality (AR), and Unmanned Aerial Vehicles (UAV).